A profile on occupational health hazards among the working class of factories in an industrial area of Bengaluru - Srinivas, Chetana; Dandiganahalli Shivaram, Priyanka (International Journal Of Community Medicine And Public Health, 2019)
Background: The occupational safety and health scenario in India is complex. The working class are victims of different occupational disorders and psychosocial stresses cause being poverty, lack of education, poor working conditions, excess working hours, etc. The morbidities include musculoskeletal disorders, generalized weakness, heart burn, endocrine disorders, injuries, etc. Hence, the present study was conducted to list the occupational health hazards of the working class of factories in an industrial area of Bangalore. Methods: The study was conducted in various factories of an industrial area in Bangalore. Socio-demographic profile, health hazards, stress, quality of life and DALY of the study subjects was assessed using a standard, pre-structured proforma. Descriptive statistics like mean and percentages was used for data analysis. Results: 384 subjects were included in the study. Majority being males i.e. 322 (86.4%) and aged 31 to 40 years, educated upto high school i.e. 342 (89%). The most commonly seen morbidities are diabetes mellitus (4.4%), hypertension (3.6%). Among the study subjects, 77% had no stress, 12.1% had mild stress and 10.7% had moderate level of stress. On assessing the quality of life, it was found that 83.5% were in good physical health, 77.6% had pain and symptoms, 96.8% were satisfied with their social relations and DALY assessment showed that diabetes was responsible for 28.42 years of life lost due to disability. Conclusions: Majority of them had no stress and diabetes was the most commonly seen morbidity.